2018
DOI: 10.1002/cmdc.201700769
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Clinically Used Bisphosphonates and Bone Mineral: from Coordination Chemistry to Biomedical Applications and Beyond

Abstract: Bisphosphonates (BPs) are well-established, widely used first-choice drugs for bone-related diseases and are one of the few classes of molecules for selective bone targeting. Their binding to calcium cations within hydroxyapatite (HA) is a key physicochemical event that takes place on the bone surface. It is the starting point for a cascade of biochemical reactions and cellular effects that lead to the pharmacological activity of BPs. The phenomenon has been known for years, yet its physicochemical nature is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 157 publications
(458 reference statements)
0
23
0
Order By: Relevance
“…In basic pH, CaL complexes (for all studied ligands) undergo one step hydrolysis to CaH –1 L (Ca(OH)L) species; the p K s of these processes lie in the range of 9.91 – 10.17 and can be assigned to deprotonation of water molecules bound to Ca 2+ . Undoubtedly, neither NH + R nitrogen nor RNH 3 + moieties do not participate in metal ion binding, in contrast to e.g., Cu 2+ , which has been found in many examples of N‐BPs both in solution and solid state . Proposed coordination models for inc and L 2 do not differ significantly from coordination of L 1 , what leads us to an assumption that the binding is implemented in the same manner with using phosphonic functions of the ligands only.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In basic pH, CaL complexes (for all studied ligands) undergo one step hydrolysis to CaH –1 L (Ca(OH)L) species; the p K s of these processes lie in the range of 9.91 – 10.17 and can be assigned to deprotonation of water molecules bound to Ca 2+ . Undoubtedly, neither NH + R nitrogen nor RNH 3 + moieties do not participate in metal ion binding, in contrast to e.g., Cu 2+ , which has been found in many examples of N‐BPs both in solution and solid state . Proposed coordination models for inc and L 2 do not differ significantly from coordination of L 1 , what leads us to an assumption that the binding is implemented in the same manner with using phosphonic functions of the ligands only.…”
Section: Resultsmentioning
confidence: 97%
“…In basic pH, CaL complexes (for all studied ligands) undergo one step hydrolysis to CaH -1 L (Ca(OH)L) species; the pKs of these processes lie in the range of 9.91 -10.17 and can be assigned to deprotonation of water molecules bound to Ca 2+ . Undoubtedly, neither NH + R nitrogen nor RNH 3 + moieties do not participate in metal ion binding, [3] [20] in contrast to e.g., Cu 2+ , [32] [39] which has been found in many examples of N-BPs both in solution and solid [39] Due to very basic constants of amine functions NH + R, which do not deprotonate in measurable range of pH for inc and L 1 correct notification should be: inc = Hinc and L 1 = HL, however, here it was omitted for simplicity as suggested for analogous compounds in the literature. [40] [b] Obtained using Hyss2009 program, based on traditional approach introduced by Schwarzenbach, [41] state.…”
Section: Interactions Of N-bps With Ca 2+ Ionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, a biodistribution study revealed that among examined radiolabeled complexes, only 177 Lu-HEDP has high bone uptake. This can be explained by the significant role of hydroxyl group which enhanced chemisorptions of OH-phosphonates, possible formation of tridentate complex and more stable binding to Ca 2+ (Gałęzowska, 2018;Palma et al, 2011). The bone uptake of the activity was observed 0.5 h post-injection and it became quite significant at 2 h. At this time point, the total skeleton was clearly visible with an insignificant accumulation of activity in any soft tissues.…”
Section: Discussionmentioning
confidence: 94%